2004
DOI: 10.1002/ajim.10334
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos in brakes: Exposure and risk of disease

Abstract: Asbestos has been incorporated into friction products since the early 1900s. Epidemiological studies have been equivocal in their analysis of the incidence of disease among mechanics servicing brakes. Decomposition of asbestos occurs during the normal usage of the brake due to thermal decomposition into forsterite, although not all asbestos is so converted. Short fibers, below 5 microm in length, are also found in brake products. Several facts are discussed including the toxicity of the remaining asbestos fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 52 publications
0
59
1
1
Order By: Relevance
“…In a recently published review article, Dr. Lemen attempted to summarize the data on asbestos exposure from brake work and the risk of mesothelioma [Lemen, 2004]. He concluded that the epidemiological evidence is equivocal.…”
Section: Re: Asbestos In Brakes: Exposure and Risk Of Diseasementioning
confidence: 98%
“…In a recently published review article, Dr. Lemen attempted to summarize the data on asbestos exposure from brake work and the risk of mesothelioma [Lemen, 2004]. He concluded that the epidemiological evidence is equivocal.…”
Section: Re: Asbestos In Brakes: Exposure and Risk Of Diseasementioning
confidence: 98%
“…Das bedeutende Gesundheitsrisiko von faserigem Antigorit wurde bereits von einer Reihe von Veröffentlichungen behandelt (Keeling et al [9]; Baumann [10]; Cardile et al [11]; Pugnaloni et al [12]; Wozniak et al [13,14] [16][17][18].…”
Section: Faseriger Antigoritunclassified
“…But refuting this scientifically untenable and highly misleading position are numerous epidemiologic studies, case reports, controlled animal experiments, and toxicological studies which show clearly and consistently that chrysotile is highly dangerous and that it is fully capable of causing cancer [14,[36][37][38][39][40][41]. These studies demonstrate that the so-called "controlled use" of asbestos is a fallacy [42]. Workers exposed to chrysotile fibers alone have excessive risks of lung cancer and excessive deaths from mesothelioma [43][44][45].…”
Section: Chrysotile Asbestosmentioning
confidence: 99%